Pemanfaatan Teknologi Augmented Reality untuk Meningkatkan Pemahaman Konsep Ilmu Pengetahuan Alam di MIS Terpadu Insan Cendikia Makassar - Nurjannariah , Nurjannariah; Najmi, Nurul; Yulianti, Nurul (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the utilization of Augmented Reality (AR) technology to enhance students’ conceptual understanding of Natural Science (Ilmu Pengetahuan Alam, IPA) at MIS Terpadu Insan Cendikia Makassar. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection in two cycles. The subjects are fifth-grade students who struggle to grasp abstract science concepts through conventional methods. Data were collected through conceptual understanding tests, observations, interviews, and documentation. The findings indicate that implementing AR technology in science learning significantly improves students’ comprehension. In the first cycle, students’ conceptual understanding increased by 28%, while in the second cycle, it improved to 50%. AR technology allows students to interact directly with three-dimensional virtual objects, making abstract concepts more concrete and easier to understand. This study concludes that the utilization of Augmented Reality technology is an effective and innovative strategy for improving science concept comprehension at the Madrasah Ibtidaiyah level.